Analisis Faktor-Faktor yang Mempengaruhi Kesiapan Calon Guru Ekonomi - Riza Yonisa Kurniawan; Hervina Renovaka Pradev Devi (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2023)
The purpose of this research is to learn how the cohort of students in the Economics Education Study Program's Pre-Service Teacher Readiness Assessment is affected by their Interest in Teaching, Self-Efficacy, and Teaching Practice. The data is analysed with WarpPLS version 7.0 and the Structural Equation Modelling (SEM) method. Preparedness to Teach was shown to be affected by the variables Interest in Teaching and Introduction to the Teaching Profession (PLP), with respective values of 0.027 and 0.001. In contrast, the effect of self-efficacy on teaching preparedness showed contrasting results, with a value of 0.183 suggesting that the two are unrelated.